Biomarkers - a possibility for monitoring of obstructive sleep apnea syndrome - Slouka, David; Kucera, Radek; Gal, Bretislav; Betka, Jaroslav; Skalova, Alena (Neuro endocrinology letters, 2019)
OBJECTIVES: Sleep apnea syndrome affects approximately 4% of adult males and 2% of adult females. It is associated with significant cardio-, cerebrovascular, metabolic and hormonal comorbidities and ranks among the more expensive medical specialties due to the requirement of high-quality technical diagnostic and therapeutic equipment as well as well-educated and experienced personnel. The aim of this study is to detect the relationship between C-reactive protein (CRP), pentraxin-3 (PTX-3), interleukin 6 (IL6), high-sensitivity troponin I (hsTnI), brain natriuretic protein (BNP) and galectin-3 serum levels and obstru-ctive sleep apnea syndrome. DESIGN: Prospective cohort study. MATERIAL AND METHODS: A group of 146 patients with middle to severe obstructive sleep apnea syndrome (OSAS) were monitored, and the results were compared with the results from a control group of healthy individuals. RESULTS: We assessed serum levels of the following biomarkers: CRP, PTX-3, IL6, hsTnI, BNP, and galectin-3. PTX-3 serum levels were statistically significantly higher (p<0.0001) in patients with OSAS, compared to controls. Statistical results related to the other biomarkers did not suggest any clinical value. ROC analysis showed that PTX-3 might be able to distinguish patients with OSAS from healthy individuals (AUC=7438). CONCLUSION: The elevation of PTX-3 serum levels is significantly associated with middle to severe obstructive sleep apnea syndrome. The PTX-3 biomarker appears to be a promising alternative method for sleep apnea syndrome investigations.
Keywords: Male; kohortové studie; biologické markery; Biomarkers; Cohort Studies; obstrukční spánková apnoe; sérový amyloidový protein; Interleukin-6; Adult; C-reaktivní protein; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; Prospective Studies; Sleep Apnea, Obstructive; syndromy spánkové apnoe; Severity of Illness Index; monitorování fyziologických funkcí; Sleep Apnea Syndromes; senioři nad 80 let; lidé; Monitoring, Physiologic; ženské pohlaví; studie případů a kontrol; interleukin-6; Humans; Aged, 80 and over; C-Reactive Protein; stupeň závažnosti nemoci; Female; lidé středního věku; Serum Amyloid P-Component; Middle Aged; prospektivní studie